2018
DOI: 10.11118/actaun201866051315
|View full text |Cite
|
Sign up to set email alerts
|

Consumption and Offer of Organic Food on the Slovak Market

Abstract: The growing interest of consumers in the products of organic farming is currently considered as a trend on the food market. The aim of the submitted paper is to characterize organic farming, the production, the offer of organic food in Slovak retails and the position of consumers on the organic food market in Slovakia. For evaluating the situation of organic farming in Slovakia, secondary data from the database of Research Institute of Agricultural and Food Economics and Central Institute of Control and Testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Other authors [34][35][36] have focused their research on the impact of the retailers' offering of organic food on consumers' behaviour. When exploring the Slovak market, Predanocyová, Šedík, Kubicová and Horská [37] found that organic products were offered by most local retailers, with milk and dairy products, and baked goods being the most popular. The assortment of organic food in stores today is in line with the customer demand and their favourite products.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [34][35][36] have focused their research on the impact of the retailers' offering of organic food on consumers' behaviour. When exploring the Slovak market, Predanocyová, Šedík, Kubicová and Horská [37] found that organic products were offered by most local retailers, with milk and dairy products, and baked goods being the most popular. The assortment of organic food in stores today is in line with the customer demand and their favourite products.…”
Section: Introductionmentioning
confidence: 99%
“…The nowadays market environment is principally characterized by the globalization, development of the market environment, intensifying competition, increasing concentration and internationalization, as well as increasing pressure on market players. The quality of managers in a network of companies with foreign capital participation, their ability to adapt to different cultures and environments, as well as their ability to properly address their subordinates come to the forefront [19,20,[99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Methodsmentioning
confidence: 99%
“…The representativeness of the sample number of food enterprises was tested by χ 2 test of good agreement (Table 2). When formulating the hypotheses, we relied on previous knowledge from our research activities [54][55][56] as well as from the research of acknowledged authors in the field of CSR [57][58][59][60][61][62][63][64][65][66].…”
Section: Methodsmentioning
confidence: 99%